2015
DOI: 10.1016/j.ejmech.2015.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Ligand binding studies, preliminary structure–activity relationship and detailed mechanistic characterization of 1-phenyl-6,6-dimethyl-1,3,5-triazine-2,4-diamine derivatives as inhibitors of Escherichia coli dihydrofolate reductase

Abstract: Gram-negative bacteria are implicated in the causation of life-threatening hospital-acquired infections. They acquire rapid resistance to multiple drugs and available antibiotics. Hence, there is the need to discover new antibacterial agents with novel scaffolds. For the first time, this study explores the 1,3,5-triazine-2,4-diamine and 1,2,4-triazine-2,4-diamine group of compounds as potential inhibitors of E. coli DHFR, a pivotal enzyme in the thymidine and purine synthesis pathway. Using differential scanni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
33
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 59 publications
3
33
1
Order By: Relevance
“…As above, the LB plots showed parallel lines further indicative of uncompetitive inhibition (Fig 3 D) and an ordered binding event whereby NADPH binding facilitates inhibitor binding. Further, this data is in agreement with reported mechanisms of DHFR inhibitors by folate-analogs 16, 23 . It has been demonstrated that the binding of and inhibition by folate-analogs is conditional to NADPH-binding 16, 23 .…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…As above, the LB plots showed parallel lines further indicative of uncompetitive inhibition (Fig 3 D) and an ordered binding event whereby NADPH binding facilitates inhibitor binding. Further, this data is in agreement with reported mechanisms of DHFR inhibitors by folate-analogs 16, 23 . It has been demonstrated that the binding of and inhibition by folate-analogs is conditional to NADPH-binding 16, 23 .…”
Section: Resultssupporting
confidence: 92%
“…However, as has been demonstrated in previous studies 16, 23 and inspection of curves at low inhibitor concentrations in Fig 3 A and Fig 3 C shows, no substrate-inhibition is seen in the absence of the inhibitor. This led us to hypothesize that the observed behavior might be indicative of a unique two-site binding inhibition mechanism displayed by ononetin.…”
Section: Resultssupporting
confidence: 87%
“…This is to ensure their utility for high-throughput experimental differential scanning fluorimetry [17, 31, 33]. Fig 4A–B shows the thermal figure, the stability curves for the wild-type FLNGLY1 and the R402XFLNGLY1.…”
Section: Resultsmentioning
confidence: 99%
“…Experimental validation of the VLS hits was carried out using a high-throughput thermal shift assay methodology following established guidelines [17, 3133]. Briefly, protein samples were dispensed into 96-well PCR plates with sypro-orange, SO, as the extrinsic fluorophore dye and thermal melting was carried out by heating the samples from 25° C–74° C using a 1° C/min heating ramp in a RealPlex quantitative PCR instrument (Eppendorf, NY, USA).…”
Section: Methodsmentioning
confidence: 99%
“…A single data point was acquired for each degree increment. The reaction was carried out in a volume of 20 μl, with 100 mM HEPES pH 7.3, 150 mM NaCl and 5 μM of the respective protein 8, 11, 26, 27 . The experiments were performed with biological replicates and the mean value was considered for further analysis.…”
mentioning
confidence: 99%